KONSEP BUDAYA TOLERANSI DAN PERDAMAIAN DALAM MEWUJUDKAN PERDAMAIAN DUNIA - Rizal Ahmaludin Setiawan; Nanang Suryana; Najmuddin Akmal; Amelia Fajri Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article examines the concept of inclusive tolerance in the Charter of Medina and its relevance to the guarantee of religious freedom in the Indonesian Constitution. The 1945 Constitution, particularly Article 28E and Article 29, provides a strong normative foundation for religious freedom, yet its implementation in practice still faces challenges such as discrimination, limited recognition of local belief groups, and administrative obstacles. The Charter of Medina, as an early political document in Islamic history, demonstrates the recognition of plurality, equality of rights, and deliberative mechanisms as the foundation for governing a diverse society. These values can serve as a historical precedent and normative inspiration for strengthening inclusive policies in Indonesia, so that religious freedom is genuinely experienced by all citizens. By linking Indonesia's constitutional principles with the historical values of the Charter of Medina, this article emphasizes the importance of building a more effective and just model for protecting religious freedom, one that is aligned with the principles of pluralism and social justice.